Design and Construction of a 1.5 kVA Pure Sine Wave Inverter for Office Use - Michael R. ADU; Blessing O. UMUKORO (FUDMA Journal of Engineering and Technology, 2026)
This paper focuses on the design and construction of a 1.5 kVA pure sine wave inverter aimed at providing an efficient and reliable power conversion solution for areas with unstable power supply. The inverter converts 12V DC from deep-cycle batteries into 220V AC, offering a stable power source for sensitive electronic devices and household appliances. Using a dsPIC30F2010 microcontroller, the system manages critical operations such as Pulse Width Modulation (PWM) control and voltage synchronization. The design includes essential components like the power stage (MOSFET/IGBT), transformer, and filtering systems, integrated through a custom-designed Printed Circuit Board (PCB). Initial testing confirmed the system’s stability under different load conditions, with a low battery cut-off at 10.1V and a charging cut-off at 14.7V. Performance evaluations showed high efficiency, particularly at mid-level loads, ensuring clean power output. The cooling system effectively managed heat dissipation, maintaining component temperatures within safe operating limits even under full load. The performance of this inverter was also compared with that of a 1.5 kVA modified sine wave inverter. The results show that the pure sine wave is better in terms of waveform and ability to carry loads, but in terms of cost and circuit complexity the modified sine wave is cheaper. Overall, the results demonstrate the inverter’s reliability and suitability for providing uninterrupted power in regions with inconsistent electricity supply.